THE EFFECT OF WORK FROM HOME ON CORPORATE CULTURE MEDIATED BY MOTIVATION, WORK BEHAVIOR, AND PERFORMANCE - Andriyanty, Reny; Komalasari, Farida; Rambe, Delila (Universitas Brawijaya, Indonesia, 2021)
The research aims to analyze how WFH influences corporate culture through the availability of work facilities, motivation, work behavior, and employee performance. It is quantitative research using structural equation modeling. Data were obtained from 32 respondents that spread across Jakarta, Bekasi, and West Java. The results of this research show that WFH significantly affects the employee's motivation. On the other hand, WFH has a significant direct effect on work motivation. Work motivation significantly affects work behavior. Work behavior affects employee performance significantly, and performance has a significant effect on innovative corporate culture. The analysis on the specific indirect effect resulted in significantly influencing innovation corporate culture from home through employee motivation, work behavior, and employee performance. Further research could explore the WFH-implementing mechanism as part of a culture of innovation for sustainable human resource development in the new-normal era of Indonesian companies